Distinct Crystal‐Facet‐Dependent Behaviors for Single‐Atom Palladium‐On‐Ceria Catalysts: Enhanced Stabilization and Catalytic Properties. Issue 16 (10th March 2022) - Hu, Botao; Sun, Kaian; Zhuang, Zewen; Chen, Zheng; Liu, Shoujie; Cheong, Weng‐Chon; Chen, Cheng; Hu, Mingzhen; Cao, Xing; Ma, Junguo; Tu, Renyong; Zheng, Xusheng; et al.
Abstract: High‐performance, fully atomically dispersed single‐atom catalysts (SACs) are promising candidates for next‐generation industrial catalysts. However, it remains a great challenge to avoid the aggregation of isolated atoms into nanoparticles during the preparation and application of SACs. Here, the evolution of Pd species is investigated on different crystal facets of CeO2, and vastly different behaviors on the single‐atomic dispersion of surface Pd atoms are surprisingly discovered. In situ X‐ray photoelectron spectroscopy (XPS), in situ near‐ambient‐pressure‐XPS (NAP‐XPS), in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), and X‐ray absorption spectroscopy (XAS) reveal that, in a reducing atmosphere, more oxygen vacancies are generated on the (100) facet of CeO2, and Pd atoms can be trapped and thus feature atomic dispersion; by contrast, on the CeO2 (111) facet, Pd atoms will readily aggregate into clusters (Pd n ). Furthermore, Pd1 /CeO2 (100) gives a high selectivity of 90.3% for the catalytic N‐alkylation reaction, which is 2.8 times higher than that for Pd n /CeO2 (111). This direct evidence demonstrates the crucial role of crystal‐facet effects in the preparation of metal‐atom‐on‐metal‐oxide SACs. This work thus opens an avenue for the rational design and targeted synthesis of ultrastable and sinter‐resistant SACs. Abstract : The distinct behaviors of single Pd atoms dispersed on different crystal facets of CeO2 is investigated. In situ characterizations reveal that the oxygen defects on the different facets of CeO2 can affect the formation and stability of single atoms. Pd atoms dispersed on CeO2 (100) exhibit higher sinter‐resistant performance than those on CeO2 (111), and a different selectivity in the N‐alkylation reaction.